Corporate Social Responsibility and Firm Performance in Chinese Listed Companies - Shi, Xiaoxian (2022)
Abstract: The purpose of this study is to demonstrate the correlation between corporate social responsibility and firm performance in Chinese listed companies. According to stakeholder theory and legitimacy theory, corporate social responsibility (CSR) has a positive effect on corporate performance. This dissertation uses a sample of 3,583 A-share enterprises listed on the Shenzhen and Shanghai stock exchanges from 2009 to 2019. Ordinary least squares (OLS) regression is used as the basic method in this paper. The result shows that there is a positive link between corporate social responsibility (CSR) and firm performance in listed firms in China. This means when companies in China have better corporate social responsibility, they can gain better financial performance. This study also conducts a series of robustness tests. In all additional tests, the results are consistent. Furthermore, by studying the impact of corporate social responsibility of Chinese listed companies on corporate performance, this paper has enriched the current literature on corporate social responsibility. Thus, this paper has implications for the development of corporate social responsibility in China and other developing countries.